Role of extrusion rate on the microstructure and tensile properties evolution of ultrahigh-strength low-alloy Mg-1.0Al-1.0Ca-0.4Mn (wt.%) alloy - X.Q. Liu; X.G. Qiao; R.S. Pei; Y.Q. Chi; L. Yuan; M.Y. Zheng (Journal of Magnesium and Alloys, 2023)
Mg-1.0Al-1.0Ca-0.4Mn (AXM1104, wt.%) low alloy was extruded at 200 °C with an extrusion ratio of 25 and different ram speeds from 1.0 to 7.0 mm/s. The influence of extrusion rate on microstructure and mechanical properties of the AXM1104 alloy was systematically studied. With the increasing of extrusion rate, the mean dynamically recrystallized (DRXed) grain size of the low alloy and average particles diameter of precipitate second phases were increased, while the degree of grain boundary segregation and the intensity of the basal fiber texture were decreased. With the rising of extrusion rate from 1.0 to 7.0 mm/s, the tensile yield strength (TYS) of the as-extruded AXM1104 alloy was decreased from 445 MPa to 249 MPa, while the elongation to failure (EL) was increased from 5.0% to 17.6%. The TYS, ultimate tensile strength (UTS) and EL of the AXM1104 alloy extruded at the ram speed of 1.5 mm/s was 412 MPa, 419 MPa and 12.0%, respectively, exhibiting comprehensive tensile mechanical properties with ultra-high strength and excellent plasticity. The ultra-high TYS of 412 MPa was mainly due to the strengthening from ultra-fine DRXed grains with segregation of solute atoms at grain boundaries. The strain hardening rate is increase slightly with increasing extrusion speed, which may be ascribed to the increasing mean DRXed grain size with rising extrusion speed. The higher strain hardening rate contributes to the higher EL of these AXM1104 samples extruded at higher ram speed.